(3YHQI GddHjH HeUQY GdcFjHs - (3GdUaOj, GdCdnHpcj, CHh GdUaGA, UdGM GdOjf, Ndjd Hf CjHc Hf YHO Gddg, J (B764(3g`s ((3bGSe Hf UGdM Hf MSjf GdEfSj GdRjOjs)
(3ChdgG (B:s
(3hdg GdMeO Ydi cd MGd hHYO MeO ddg Mb MeOgEffj deG hbaJ Ydi GdQSGdI GdJj CfTCgGYdGA GdOjf YHO GdXGgQhCMHHJ Cf CMPh MPhg QSGdI JMJhj Ydi GdefXhe hGdefKhQhSejJgG HYHQI GddHjHs
(3BNQgG (B:s
(3hdG RGO ddEfSGf CaVd eQJbG EPG SGbg fMh GdefjI MGOi aWhHi dYHO bO JfHg WQag dMGd UdGM ef efGe aSGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 315s
(3eYLe GdeDdajf(B: 1 / 680s
(3cTa GdXfhf(B: 2 / 1123s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs